Analisis Memberi Makan Banyak Orang Dan Implementasinya Pada Masa Kini (2 Raja-Raja 4:42-44) - Selviana Putri Naibaho; Nino Sampe Tindih Sitohang; Herdiana Sihombing (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2023)
This article discusses the importance of feeding many people and its implementation today. Nowadays, challenges such as poverty, hunger and unequal access to food are still serious problems in various places. This article aims to analyze the importance of feeding many people and present several implementations that can be done to overcome this problem, and also provide teaching that can influence and encourage people to help each other and foster a sense of empathy with others. In this research, the author analyzes and interprets text from the Bible 2 Kings 4:42-44. This book tells about the history of the reign of several Kings in the Kingdom of Israel and the Kingdom of Judah, especially in this verse which focuses on the Miracle performed by the Prophet Elisha on one hundred people through God's blessing. Teaching in Christianity teaches the values of compassion, social care, and service to others. Through a qualitative approach, this paper explores how Christian values such as responsibility, love and kindness can be applied in feeding efforts involving large numbers of people. The results of this paper highlight the important role of Christian teachings in shaping food programs, both in supporting communities in need and managing food programs that are in accordance with Christian religious values and relevant to current social dynamics.